The mechanisms of inflammation in gout and pseudogout (CPP-induced arthritis) - H.-K. Ea; N. Busso (PAGEPress Publications, 2012)
Recent advances have stimulated new interest in the area of crystal arthritis, as microcrystals can be considered to be endogenous "danger signals" and are potent stimulators of immune as well as non-immune cells. The best known microcrystals include urate (MSU), and calcium pyrophosphate (CPP) crystals, associated with gout and pseudogout, respectively. Acute inflammation is the hallmark of the acute tissue reaction to crystals in both gout and pseudogout. The mechanisms leading to joint inflammation in these diseases involve first crystal formation and subsequent coating with serum proteins. Crystals can then interact with plasma cell membrane, either directly or via membrane receptors, leading to NLRP3 activation, proteolytic cleavage and maturation of pro-interleukin-1β (pro-IL1β) and secretion of mature IL1β. Once released, this cytokine orchestrates a series of events leading to endothelial cell activation and neutrophil recruitment. Ultimately, gout resolution involves several mechanisms including monocyte differentiation into macrophage, clearance of apoptotic neutrophils by macrophages, production of Transforming Growth Factor (TGF-β) and modification of protein coating on the crystal surface. This review will examine these different steps.